Use of Cadaveric Pericardial Tissue in the Surgical Treatment of Neurogenic Bladder - Madison Caja; Michaela Lamonde; John Barnard; Stanley Zaslau; Robert E. Shapiro (Case Reports in Urology)
The surgical treatments for neurogenic bladder are extremely variable. The lack of specific treatment guidelines makes this disease process even more challenging to treat. We present a case of a 55-year-old female with neurogenic bladder secondary to spinal cord injury (SCI). Her incontinence was conservatively managed with indwelling Foley drainage. Despite continued upsizing of the Foley catheters, the patient continued to have urinary leakage. The patient subsequently underwent a transvaginal bladder neck closure (BNC) with suprapubic bladder neck diversion (SPC). The urethra was successfully closed and uniquely supported with the use of cadaveric pericardial tissue (CPT). This surgical approach of neurogenic bladder provides durable continence with short operative times, minimal patient morbidity, decreased hospital length, and low risk of progressive renal dysfunction. BNC with SPC can provide an excellent management solution for neurogenic bladder from spinal cord injury refractory to conservative management.